ANALISIS KONSUMSI ENERGI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) KENDARI - Samhuddin, Samhuddin; Kadir, Kadir; Syahrun, Muhammad (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
Electricity consumption level of construction or building can be determined by calculating the amount of electrical energy used in a certain time. This study aims to determine electricity consumption levelat KPKNL Kendari. According to the standards set by the 2000 National Standardization Agency for efficient energy for an office building is 240 kWh/m2. Refers to this standard, electricity consumption level of KPKNL Kendari was investigated. To aim the study goals, observation of load used and electrical energy was done. Various load used leads to electricity consumption which measured by dividing total electricity consumption to total building area, known as energy consumption intensity value (Intensitas Konsumsi Energi/IKE). Total electricity consumption for a year was 82,042 kWh and total building area is 913,8 m2. KPKNL Kendari’sIKE is 89.8 kWh / m2, this result shows that KPKNL Kendari electricity consumption Level is efficient. Keywords: Electrical energy, electricity cost, energy consumption intensity.